Prevalence of Biofilm Genotype Pattern( algD −/pslD −/pelF –) with Multidrug-Resistant in Clinical Local Pseudomonas Aeruginosa Isolates - Duraid K. AlRawi; Huda M. Mahmood (Institute of Medico-legal Publications Pvt Ltd, 2022)
The study was designed to explore the distribution and association of the biofilm genotype pattern(algD −/pslD −/pelF –) with multidrug-resistant in clinical local Pseudomonas aeruginosa isolates. Atotal of one hundred isolates of Pseudomonas aeruginosa were included in this study, which has beencollected from different specimens, from July to September 2020. The isolates included were 34 fromburns, 19 from wounds, 23 from ear infections, 22 from urinary tract infections (UTI), and 2 from cysticfibrosis (CF). Identification of the isolates was carried out using microscopical, cultural characterizationon MacConkey agar, Cetrimide agar, then Pseudomonas agar. Biochemical tests were performed, andfurther identification was carried out by the VITEK_2_compact system. Genotypic identification hasbeen completed by16SrRNA. To assess the frequency of multidrug-resistant of Pseudomonas aeruginosa(MDR), the antibiotic susceptibility test was done. It was carried out by using different groups ofantibiotics (10 antibiotics) using the Kirby–Bauer disk diffusion method. The results showed that theresistance were Ceftazidime(62%),Gentamicin(26%,(Piperacillin-tazobactam(25%), Ticarcillin(24%),Meropenem(20%), Cefepime (18%),Amikacin(17%) Levofloxacin(16%), Colistin(15%) Imipenem(10%).Biofilm production was assessed using a microplate examination method. The results showed that 93%of isolates were positive for biofilm production, while (7%) were non-biofilm producers. There weredifferences in the rates of biofilm-production distributed into 21 (21%) were strong biofilm producer(OD was more than 2.156), 25 (25%) intermediate biofilm producer, and 47 (47%) were weak biofilmproducer (OD was less than 1.078), and the non -biofilm producer was 7(7%).Three virulence factors genes ( algD, pslD, and pelf ) were chosen, which responsible for the phenotypicpattern of biofilm formation and identified as genotypic algD −/pslD −/pelF – pattern. The differencesin genotypic pattern prevalence among the MDR-positive isolates of different origins were statisticallysignificant. Chi-square analysis showed a highly significant association between strong biofilm capacityand genotype pattern (p<0.0001), also the analysis showed a highly significant association betweenmoderate biofilm capacity and genotype pattern (p<0.002). Chi-square analysis showed a highlysignificant association between weak biofilm capacity and genotype pattern ( p<0.001).In the current study the percentage of resistance among P. aeruginosa local isolates for multiple antibiotics(MDR) was relatively low, maybe due to the combination strategies based on appropriate anti-pseudoantibioticagents that may be used to improve treatment from the related infections, according to theseresults, P. aeruginosa local isolates that produced biofilm were mostly (70%) indicated as non-MDR.